ANALISIS KINERJA SIMPANG TIGA TAK BERSINYAL (STUDI KASUS JALAN SUDIRMAN – R A KARTINI PAYAKUMBUH UTARA) - Azmi, Rifki; Gusmulyani, Gusmulyani; Nurhasanah Habirun, Asiya (Ensiklopedia Research and Community Service Review, 2024)
Road intersections are places where traffic flows from two or more roads meet. Road network performance must take into account the delay due to intersections, both signal intersections and barriers, the high population of vehicles that are not matched by the availability of adequate infrastructure of the road. Analyzing the capacity and performance level of an unsignalized deviation is data from the field, in the form of geometric intersection data (width of each intersection leg), the equivalence number of each vehicle, so that uniformity in the car is obtained passenger (SMP). Then the capacity and level of intersection performance are calculated, which includes the degree of saturation, and the deviation delay with the Indonesian Road Capacity Manual method (MKJI 1997). The results of the analysis obtained, the capacity value (C) of the three observation days, the biggest value is 2362,626cu/hour, the degree of saturation (DS) is 0.566 sec/smp, and delay (D) deviation of 10,831sec / smp. Then obtained the level of service at the intersection of Jl. Sudirman – Jl.R.A. Kartini north Payakumbuh is still able to accommodate traffic volume, because the degree of saturation is still small and the level of delay assessment is still in criteria B, so there is no need to recalculate the unsigned intersection Jl. Sudirman – Jl. R.A. Kartini north Payakumbuh. Keywords : Unsignalized intersections, road performance, side barriers, intersections